The route to take-up: raising incentives or lowering barriers? - Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2008)
This paper investigates which measures are effective in promoting the take-up of welfare support by needy individuals, considering both financial incentives and policies intended to lower claiming costs. The analysis uses an exogenous policy change, the introduction of the Pension Credit in the United Kingdom in 2003, that reformed the income support scheme available to pensioners. While increasing the entitlement amount for a subgroup of eligible pensioners, the Pension Credit introduction was accompanied by other complementary measures, including an advertisement campaign, reformed `light touch administration and a more claimant-friendly application procedure. The behavioural response to such exogenous changes is identified using parametric and non parametric analysis of repeated cross sections of Family Resources Survey data. Results consistently show the efficacy of increased financial incentives as take-up triggers, while no effect is found for the `lowering barriers policies when unaccompanied by concurrent raised monetary rewards.
Keywords: 330